Modeling the forecast of solar energy generation and economic analysis of the implementation of photovoltaic panels at the IFNMG campus Teófilo Otoni - Rocha, Larissa Guimarães; Medeiros, Marcos Oliveira; Pereira, Luan Diego de Lima (Brazilian Journal of Production Engineering, 2021)
Considering the optimistic scenario of the generation of solar energy in Brazil, this paper presents a modeling of the generation forecast of solar energy of a solar power plant implanted in the Federal Institute of the North of Minas Gerais (IFNMG) campus Teófilo Otoni - MG. The methodology used requires the analysis of historical data of the solar irradiation and temperature of the study region and the use of Monte Carlo Simulation to determine the energy generation forecast. In order to minimize the error caused in using average data of the stochastic variables, modeling of the stochastic dependence between temperature and solar irradiation was performed. Based on this modeling, an economic analysis of the consumption of the IFNMG campus Teófilo Otoni was made, making it possible to forecast the savings generated by the distributed generation system.